Transitional Care of Older Adults from Hospital to Home - Chuansangeam, Mallika (Asian Medical Journal and Alternative Medicine, 2023)
Older adults often have reduced body reserve, multiple illnesses of many organ systems, and receive polypharmacy thus requiring complex medical care. Older adults have the opportunity to be cared for in different settings leading to changes in all dimensions of care. This creates a chance for medical mistakes and affects the safety of older adults that come with each transition of care. Transitional care is especially important in older adults. Fast and important information transfer between care teams who provide information to patients and caregivers in a language that is easy to understand is vital. Involving patients in the decision-making review of medication use and follow-up after the patient leaves the hospital contributes to reducing the chance of hospital readmission of the patient. This requires cooperation from a multidisciplinary team. Effective transitional care improves the quality of life and reduces the cost of treating older adults. Objectives: This review aimed to indicate the importance of effective transitional care. The review consisted of examples of transitional care models and components of each model. Also, specialized care in disease specific patients were mentioned.